Identifikasi Bahaya Dan Penilaian Resiko Upaya Mengurangi Tingkat Kecelakaan Di Area Logistik Pada PT Osi Electronics - Ardiman Situmeang; Ganda Sirait (Prosiding, 2020)
HIRARC is one way of preventing potential hazards that exist in each type of work.Steps begin by way of danger, then assess the risk and perform the control. PT OSIElectronics has a logistics area as a place to receive or delivering of goods that using forklifts. For that researchers interested to be held in the area. This research is a qualitative research. Techniques used in data collection are field HIRARC observation,company document, and interview. Calculates data starting with risk value with score form. Based on the results of the research, it is known that there are 6 types of activities in logistic areas that have different source of danger. In terms of safety still have some deficiencies, especially safety on APD equipment, as well as awareness of the workers.Suggestion from the researcher is that company will improve safety at every job in logistic area to reduce unsafe action and unsafe condition. For APD equipment should be emphasized as well as awareness of the workers in maintaining safety at work and distinguishing specific paths for forklifts and people.